Karakteristik Roti Manis dengan Penambahan Tepung Jagung (Zea Corn L.) sebagai Makanan Sumber Serat - Tri Gelish Nopita Budi; Diah Ratnasari; Sulasyi Setyaningsih (Jurnal Kesehatan Amanah, 2026)
Sweet bread is one of the bakery products that is popular among consumers, but is generally low in dietary fiber. The addition of fiber in bread can improve the health benefits and nutritional quality of the product. High-fiber sweet bread with the addition of corn flour has been formulated and characterized to increase its fiber content. This study aims to determine the sensory characteristics and dietary fiber content of sweet bread products with the addition of corn flour. In this study, using a completely randomized design (CRD) research method, bread was made with several formulations containing a ratio of corn flour and wheat flour, namely (1) 0: 100; (2) 20: 80; (3) 30: 70; (4) 40: 60; (5) 50: 50 (%) with 3 repetitions. The results of the color sensory test on sweet corn flour bread ranged from 1.57-3.29 (brownish yellow) with a P value = 0.000. The taste of sweet corn flour bread ranged from 3.14-3.69 (very sweet) with a P value = 0.037. The aroma of sweet corn flour bread ranges from 2.23-2.17 (fragrant) with a P value of 0.175. The texture of sweet corn flour bread ranges from 2.40-3.06 (soft) with a P value of 0.014. The dietary fiber content of sweet corn flour bread ranges from 19.26%-53.68% with a P value of 0.021. The proportion of corn flour and wheat flour does not affect the aroma of sweet bread. The proportion of corn flour and wheat flour significantly affects the color, taste, texture, and dietary fiber content.